Replicating different roles of intent across moral domains - Sweetman, Joseph (R Soc Open Sci, 2020)
Whether moral cognition is underpinned by distinct mental systems that process different domains of moral information (moral pluralism) is an important question for moral cognition research. The reduced importance of intent (intentional versus accidental action) when judging purity (e.g. incest), when compared with harm (e.g. poisoning), moral violations is, arguably, some of the strongest experimental evidence for distinct moral systems or ‘foundations’. The experiment presented here is a replication attempt of these experimental findings. A pre-registered replication of Experiment 1B from the original article documenting this effect was conducted in a sample of N = 400 participants. Findings from this successful replication are discussed in terms of theoretical and methodological implications for approaches to moral cognition.